Assessing the regional potential for industrial symbiosis - Olga A. Chernova (Journal of New Economy, 2024)
The ever-increasing negative impact of economic growth on the environment dictates the need to introduce business models of the circular economy based on the principles of industrial symbiosis. However, for the development of industrial symbiosis, it is necessary not only to understand its essence and possible benefits, but also to assess the readiness of a regional economy to implement symbiotic interactions. The purpose of the article is to develop tools for assessing the regional potential for industrial symbiosis. The research methodology is based on the concept of industrial symbiosis and Kleiner’s systems paradigm. The study applies index and matrix methods. The evidence is the data on the regions of the Southern Federal District for 2021–2022 taken from the Federal Service for Supervision of Natural Resources and the Federal State Statistics Service of the Russian Federation. The paper presents an original toolkit for assessing the regional potential for industrial symbiosis, which includes a system of indicators for evaluating its main components and a typology of regions according to the level of potential for industrial symbiosis. According to the findings, the Rostov and Astrakhan oblasts, as well as the Republic of Crimea hold the greatest potential for the development of symbiotic interactions. The study advances theoretical contributions in the field of circular economy in terms of understanding the factors and conditions necessary for the implementation of industrial symbiosis processes in a region. The practical significance of the work lies in the possibility of using its results to devise methodological approaches to the design of industrial symbiosis projects as an element of the regional socioeconomic development strategies.